Elasticity of Energy Intensity on a Regional Scale: An Empirical Study of International Trade Channel - Burakov, Dmitry (International Journal of Energy Economics and Policy, 2016)
This study examines the relationship between energy intensity in different world regions. To explain relationship between them we test a hypothesis of international trade channel and determine degree of sensitivity of national economy’s energy intensity to actions of major competitors in export market. Based on data of energy intensity for more than 150 countries for the period from 1980 to 2011, using regression analysis, we built a number of unrestricted VAR models reflecting relationship between energy intensity of different regions, and relationship between groups of economies, primary source of exports for which is fuel or engineering sector. To characterize elasticity of energy intensity in sampled countries, we use variance decomposition and impulse response techniques. The study shows the presence of a stable relationship between energy intensity for different regions of the world. Testing interlinkages between energy intensity of economies exporting raw materials (e.g. oil) and engineering production, for trade channel, confirms its existence. The sensitivity of economies exporting raw materials to shocks in energy intensity tends to be significantly lower than in economies exporting consumer goods. Keywords: energy intensity; elasticity of energy intensity; credit market. JEL Classifications: F14; O13; Q43